EXPLORING THE INTERPLAY OF SELF-ESTEEM, GRATITUDE, AND SUBJECTIVE WELL-BEING AMONG MUSLIM UNIVERSITY STUDENTS IN STATE ISLAMIC UNIVERSITY OF NORTH SUMATRA INDONESIA - Batubara, Syauqina; Hardjo, Suryani; Dewi, Salamiah Sari (UIN Sumatera Utara, 2025)
Abstract: This study examines the relationship between self-esteem, gratitude, and the subjective well-being of students at the Faculty of Tarbiyah and Teacher Training (FITK), State Islamic University of North Sumatra. Employing a quantitative research design, the study utilizes both simple and multiple correlation analyses. The results indicate a significant correlation between self-esteem and subjective well-being (r = 0.878), as well as between gratitude and subjective well-being (r = 0.899), demonstrating strong associations in both cases. Furthermore, the multiple correlation analysis yields a combined correlation coefficient (R) of 0.911, suggesting that self-esteem and gratitude jointly account for 91.1% of the variance in students' subjective well-being. These findings indicate that both factors contribute substantially to enhancing students' overall psychological well-being. Consequently, programs designed to foster self-esteem and gratitude may have a positive impact on students' mental health and emotional resilience.Keywords: Gratitude, self-esteem, subjective well being